Finely Grinding Cereal Grains in Pelleted Diets Offers Little Improvement in Nursery Pig Growth Performance - G. E. Bokelman; J. A. De Jong; J. R. Kalivoda; A. Yoder; C. R. Stark; J. C. Woodworth; C. K. Jones (Kansas Agricultural Experiment Station Research Reports, 2015)
Five experiments were conducted to determine the effects of corn particle size and diet form on nursery pig performance and feed preference. In Exp. 1, 192 nursery pigs (PIC 327 × 1050; initially 14.7 lb and 26 d of age) were used in a 35-d experiment. Pens of pigs were balanced by BW and allotted to 1 of 4 treatments with 6 pigs per pen and 8 pens per treatment. The same corn and soybean meal-based diet formulation was used for all treatments. The 2 × 2 factorial consisted of the main effects of corn particle size (400 vs. 700μm) and diet form (mash vs. pelleted). Pigs fed mash diets had improved overall ADG and greater ADFI during all periods (P<0.05) and particle size did not impact (P>0.10) performance. In Exp. 2, a study utilized 96 pigs to evaluate feed preference of pigs consuming mash diets with either 400 or 700μm corn. Pigs overwhelmingly (P<0.05) preferred to consume 700μm corn compared to 400μm corn (79.3 vs. 20.7%). In Exp. 3, 224 nursery pigs (PIC 327 × 1050; initially 24.1 lb and 40 d of age) were used in a 10-d experiment to determine the effects of corn particle size in pelleted diets on nursery pig performance. Experimental treatments were formed by grinding corn to 1 of 4 different particle sizes (250, 400, 550, or 700μm). Particle size tended to affect (P<0.10) ADG in a quadratic manner, but did not impact (P>0.10) ADFI or F/G. Pigs fed pelleted diets from either 250 or 700μm corn had poorer ADG than the intermediate treatments. Exp. 4 utilized 91 pigs to evaluate the preference of pigs consuming pelleted diets with either 250 or 700μm corn from Exp. 3. Even in pelleted form, pigs preferred (P<0.05) to consume diets manufactured with the coarser particle size corn (58.2 vs. 41.8%). In Exp. 5, 180 nursery pigs (PIC 327 × 1050; initially 15.8 lb and 36 d of age) were used in a 35-d experiment to determine the effects of corn particle size and pelleting on nursery pig growth performance. The 2 × 2 factorial consisted of 2 corn particle sizes (500μm vs. 750μm) and two diet forms (mash vs. pelleted). Overall, reducing particle size from 750 to 500μm did not affect growth performance (P>0.10). Pelleting reduced (P<0.05) feed intake, but did not affect ADG or F/G (P>0.10). These studies suggest that there is little value to be gained by grinding corn to less than 700 microns if fed in pelleted form. Furthermore, our data suggest that, regardless if fed as mash or pellets, pigs prefer to consume diets manufactured with coarser ground corn if given the choice.
Keywords: mash; nursery pig; particle size; performance; pelleting